સાબિત કરો કે : $\cos ^{2} 2 x-\cos ^{2} 6 x=\sin 4 x \sin 8 x$
It is known that
$\cos A+\cos B=2 \cos \left(\frac{A+B}{2}\right) \cos \left(\frac{A-B}{2}\right), \cos A-\cos B=-2 \sin \left(\frac{A+B}{2}\right) \sin \left(\frac{A-B}{2}\right)$
$\therefore$ $L.H.S.$ $=\cos ^{2} 2 x-\cos ^{2} 6 x$
$=(\cos 2 x+\cos 6 x)(\cos 2 x-6 x)$
${ = \left[ {2\cos \left( {\frac{{2x + 6x}}{2}} \right)\cos \left( {\frac{{2x - 6x}}{2}} \right)} \right]}$
${\left[ { - 2\sin \left( {\frac{{2x + 6x}}{2}} \right)\sin \left( {\frac{{2x - 6x}}{2}} \right)} \right]}$
${ = [2\cos 4x\cos ( - 2x)][ - 2\sin 4x\sin ( - 2x)]}$
${ = [2\cos 4x\cos 2x][ - 2\sin 4x( - \sin 2x)]}$
${ = (2\sin 4x\cos 4x)(2\sin 2x\cos 2x)}$
${ = \sin 8x\sin 4x = R.H.S}$
$\frac{{\sec 8A - 1}}{{\sec 4A - 1}} = $
$\frac{{3 + \cot {{76}^o}\cot {{16}^o}}}{{\cot {{76}^o} + \cot {{16}^o}}}$ =
સાબિત કરો કે : $\sin ^{2} 6 x-\sin ^{2} 4 x=\sin 2 x \sin 10 x$
$\tan \alpha + 2\tan 2\alpha + 4\tan 4\alpha + 8\cot \,8\alpha = $
જો $\tan x = \frac{{2b}}{{a - c}}(a \ne c),$
$y = a\,{\cos ^2}x + 2b\,\sin x\cos x + c\,{\sin ^2}x$
અને $z = a{\sin ^2}x - 2b\sin x\cos x + c{\cos ^2}x,$ તો